Sensory function in headache: a comparative study among patients with cluster headache, migraine, tension-type headache, and asymptomatic subjects - Malo-Urriés, Miguel; Estébanez-de-Miguel, Elena; Bueno-Gracia, Elena; Tricás-Moreno, José Miguel; Santos-Lasaosa, Sonia; Hidalgo-García, César (Neurological sciences, 2020)
Aims Studies evaluating sensory function of the entire trigeminocervical region in patients with cluster headache (CH), migraine (MH), and tension-type headache (TH) are required. The purpose of the present study was to evaluate and compare sensory function in the trigeminocervical region in patients with CH, MH, and TH and healthy controls (HC). Methods Quantitative sensory testing (QST), including pressure pain threshold (PPT), tactile detection threshold (TDT), prick detection threshold (PDT), and two-point detection threshold (2PDT), was evaluated in 139 patients with headache (CH = 16, MH = 52, TH = 71) and 30 HC. Test sites included bilaterally the first, second, and third divisions of trigeminal nerve (V1, V2, and V3), cervical spine, and thenar eminence. Results TH presented significantly lower PPT values compared with CH ( p < 0.015), MH ( p < 0.048), and HC ( p < 0.009), while MH demonstrated significantly lower values than HC ( p = 0.001–0.023). When analyzing TDT, CH in the symptomatic side presented significantly higher values in V1 compared with MH ( p = 0.001), TH ( p < 0.001), and HC ( p < 0.001) and in V2 compared with TH ( p = 0.035). No statistically significant differences were found for PDT ( p > 0.005). With regard to 2PDT, CH-s presented significantly higher values in V1 with respect to HC ( p = 0.016) but lower values in V2 compared with MH ( p < 0.001) and TH ( p = 0.003). Conclusion The results of the present study indicate specific and different altered mechanical sensory thresholds in CH, MH, and TH patients compared with HC subjects.